2017
DOI: 10.5539/sar.v6n2p1
|View full text |Cite
|
Sign up to set email alerts
|

Farmers Perception of Low Soil Fertility and Hybrid Maize and the Implications in Plant Breeding

Abstract: In spite of efforts by national and international scientists to improve crop productivity, varieties of crops grown in Africa have low productivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Farmers' preference for nitrogen use efficient varieties could be a risk coping strategy, a perceived economical way of improving their maize yields without overly depending on chemical fertilizers. The findings of Ribeiro et al (2017) revealed low soil fertility as the most dominant constraint in maize productivity in Wenchi and Ejura Sekyedumase districts in Ghana. In Angola, Mozambique, and Zimbabwe, a variety's performance under poor soil fertility is an important trait considered along with yield potential in the selection of an ideal maize variety by farmers (Kassie et al 2012).…”
Section: Trait Preferences Of Maize Value Chain Actors In the Study Areasmentioning
confidence: 94%
See 2 more Smart Citations
“…Farmers' preference for nitrogen use efficient varieties could be a risk coping strategy, a perceived economical way of improving their maize yields without overly depending on chemical fertilizers. The findings of Ribeiro et al (2017) revealed low soil fertility as the most dominant constraint in maize productivity in Wenchi and Ejura Sekyedumase districts in Ghana. In Angola, Mozambique, and Zimbabwe, a variety's performance under poor soil fertility is an important trait considered along with yield potential in the selection of an ideal maize variety by farmers (Kassie et al 2012).…”
Section: Trait Preferences Of Maize Value Chain Actors In the Study Areasmentioning
confidence: 94%
“…This allows plant breeders to interact with farmers and other actors to set breeding objectives and share responsibility for decision-making, implementation, and generation of products (Morris and Bellon 2004). Participatory plant breeding (PPB) approaches have been extensively used in cultivar development programs to address farmers' needs and their socioeconomic situation as well as consumers' preferences (Kamara et al 2006;Tetteh et al 2011;Dao et al 2015;Ajambo et al 2017;Ribeiro et al 2017). For example, Sibiya et al (2013) used the PPB approach in three villages in KwaZulu-Natal and reported that farmers preferred maize varieties with high yield and prolificacy, disease resistance, early maturity, white grain endosperm color, and drying and shelling qualities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 30 improved varieties of maize were developed and released in Ghana between 1942 and 2014 (Ribeiro et al, 2017). Despite the efforts made by agricultural extension personnel in helping to make these varieties available to farmers, maize productivity is still low (Ribeiro et al, 2017;Yeboah, 2013;Ragasa et al, 2014;.…”
Section: Issues Of Compliance With Production Practicesmentioning
confidence: 99%
“…Data were analysed using the Statistical Package for Social Scientists (SPSS), version 20 and Excel, which are widely used packages for data summarising and statistical analysis (MacDonald & Headlam, 2008). Variables were described based on the descriptive statistics namely frequency counts, percentages and graphs, an approach also employed by Ribeiro (2017). …”
Section: Data Collection Methods Sampling and Data Analysismentioning
confidence: 99%